The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/eqe.434
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear viscoelastic modelling of earthquake-induced structural pounding

Abstract: SUMMARYPast severe earthquakes indicate that structural pounding may cause considerable damage or even lead to collapse of colliding structures if the separation distance between them is not su cient. Because of its complexity, modelling of impact is an extremely di cult task, however, the precise numerical model of pounding is essential if an accurate structural response is to be simulated. The aim of this paper is to analyse a non-linear viscoelastic model of collisions which allows more precise simulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
299
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(311 citation statements)
references
References 26 publications
2
299
0
10
Order By: Relevance
“…Kasai and Maison [12] investigated the building pounding damage during the 1989 Loma Prieta earthquake. Jankowski [13] presented nonlinear viscoelastic modelling of earthquake-induced structural pounding. Jankowski [14] reported that the increase in structural damping of adjacent structures simultaneously leads to the extension of the region in the spectrum where the impact force is equal to zero.…”
Section: Introductionmentioning
confidence: 99%
“…Kasai and Maison [12] investigated the building pounding damage during the 1989 Loma Prieta earthquake. Jankowski [13] presented nonlinear viscoelastic modelling of earthquake-induced structural pounding. Jankowski [14] reported that the increase in structural damping of adjacent structures simultaneously leads to the extension of the region in the spectrum where the impact force is equal to zero.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with these models, a negative reaction force takes place just before the end of the contact. More recently, Hertz models have been used [1,12]. They provide a better fit with experimental results, although there are not many of them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have been chosen instead of the Hertz models because parameter selection as well as numerical solution is easier. Also, visco-elastic elements make it easy to fix parameters so as to fit experimental reaction forces [1]. Parameters M,K S ,C S and Kb are not difficult to obtain.…”
Section: The Model and Its Integrationmentioning
confidence: 99%
See 2 more Smart Citations